3-PGDH Deficiency, Seizures, and Microcephaly - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The beneficial effects of oral L-serine (up to 500 mg/kg/day) and glycine (200 mg/kg/day) in 2 siblings, aged 7 and 5 years, with 3-phosphoglycerate dehydrogenase (3-PGDH) deficiency are reported from University Children's Hospital, Utrecht, The Netherlands.